Utilization of Suji Leaves Extract (Pleomele Angustifolia N.E Brown) in Inhibiting Carrageenan-Induced Inflammation on Rats - Koja, Reni; Prangdimurti, Endang; Giriwono, Puspo Edi (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2024)
Suji leaf (Pleomele angustifolia N.E. Brown) has long been used as an ingredient for traditional medicines. This study seeks to evaluate the anti-inflammatory activity of suji leaf extract in terms of its ability to reduce oedema in the hind paws of rats. Six groups were treated: negative control, positive control given diclofenac sodium as anti-inflammatory medication, two groups of suji leaf extract powder (SEP) with doses of 300 and 800 mg/kg, acetone extract of suji leaf (AES), and a group of acetone extract of SEP (EA-SEP) at a dose of 500 mg/kg with oral administration. Injections of 1% carrageenan suspension into the right hind paw of rats induced inflammation. The results demonstrated that SEP administered at a dose of 800 mg/kg has an inflammatory capacity (80.56%), AES (56.94%), and AE-SEP (75.7%). Chlorophyll, total phenol, and antioxidant capacity in SEP (9.0809 mg /g sample; 3.7354 mg GAE/g sample; 3.04 mg AAE/g sample), AES (4.6471 mg /g sample; 0.9994 mg GAE/g sample; 3.26 mg AAE/g sample), and AE-SEP (6.4912 mg /g sample; 2.1703 mg GAE/g sample; 2.55 mg AAE/g sample). According to qualitative test results, Suji extract contains bioactive compounds of the flavonoid group, saponins, steroids, and triterpenoids. It is believed that phenolic compounds function as anti-inflammatory agents.